Theory and Practice of Neuromarketing: Analyzing Human Behavior in Relation to Markets - BoÄkovÃ¡, KateÅ™ina; Å krabÃ¡nkovÃ¡, Jana; HanÃ¡k, Michal (Ital Publication, 2021)
The presented paper deals with a comprehensive interpretation of the term neuromarketing, as a discipline that applies neuroscientific methods to analyze and to understand human behavior in relation to markets and market exchanges. Due to the topic, this paper presents mainly secondary data, next the questionnaire is used. We state that neuromarketing is a discipline that applies neuroscientific methods to analyze and to understand human behavior in relation to the markets and market exchanges. Each of the neuromarketing techniques measures different data and suits different purposes, with a combination of the most reliable results. The interest in the theoretical research of neuromarketing focuses on the consumer decision-making process. One of the main benefits of neuromarketing is the potential to measure accurate, objective data that can be used to make informed decisions in management practice. However, it is currently only a complement to other areas of marketing and will be beneficial if it is used to obtain otherwise inaccessible data. We are convinced that the existence of the Neuromarketing Center in the ITI of the Olomouc agglomeration will be a significant contribution to the development of the neuromarketing theory.Â Doi: 10.28991/esj-2021-01256 Full Text: PDF